2020
DOI: 10.1080/00313831.2020.1788149
|View full text |Cite
|
Sign up to set email alerts
|

Pupils’ Perceptions About Technology-enhanced Feedback: Do Emojis Guide Self-regulated Learning?

Abstract: Although technology-enhanced feedback (TEF) from teachers to pupils is given daily, little is known about pupils' thoughts about this feedback in Finland.Pupils' perceptions were studied to evaluate whether TEF support self-regulated learning, as suggested. Interviews (N=62) and questionnaires (N=132) about pupils' perceptions and emotions related to TEF were analysed. TEF, enriched with smiling emojis, is used to monitor performance and behaviour. Reported emotions varied from joy to disappointment. TEF seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Regarding SRL strategies, Kim et al (2015) found that diligent students often mentioned using SRL strategies. In the Finnish context, SRL has been studied from several perspectives, such as the relationship between emojis and SRL (Oinas et al, 2020), pupils' readiness for SRL (Metsärinne et al, 2015) and disciplinary and gender differences in SRL strategies (Virtanen & Nevgi, 2010). Additionally, previous research has shown that many Finnish students start their university path with inadequate learning strategies and have poor skills for regulating their learning (Lonka & Lindblom-Ylänne, 1996;Virtanen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding SRL strategies, Kim et al (2015) found that diligent students often mentioned using SRL strategies. In the Finnish context, SRL has been studied from several perspectives, such as the relationship between emojis and SRL (Oinas et al, 2020), pupils' readiness for SRL (Metsärinne et al, 2015) and disciplinary and gender differences in SRL strategies (Virtanen & Nevgi, 2010). Additionally, previous research has shown that many Finnish students start their university path with inadequate learning strategies and have poor skills for regulating their learning (Lonka & Lindblom-Ylänne, 1996;Virtanen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on students' responses to digital feedback have shown that this does not promote learning and instead just leads to feelings of disappointment, worry, and rage (Oinas et al, 2021).…”
Section: Positive Home-school Communicationmentioning
confidence: 99%